Caféiculture Et Accès Aux Soins De Santé Au Burundi : Analyse De La Dynamique Des Mutuelles De Santé Des Caféiculteurs De La Province Kayanza Au Nord Du Burundi - Alexis, Ndabarushimana (European Scientific Journal, ESJ, 2018)
This article highlights the dynamics of health mutuals of coffee farmers in Kayanza province. It shows the factors related to difficulties in accessing health care for coffee growers in Kayanza province. These factors are fundamentally linked to the socio-economic environment that structures the living conditions of coffee growers in a world where the Burundian government has opted a ‘‘laissez-faire’’ and ‘‘laissez-aller’’ policy in the coffee sector. In order to do this, we opted for qualitative approaches with the use of the interview guide and quantitative with the use of a questionnaire administered directly to the coffee growers of Kayanza province. In this situation of self-determination of coffee growers, this article highlights the constraints faced by mutual health organizations in their mission to be able to access health care quality of coffee farmers after having shown the role played by mutuals and FEMUSCABU in promoting the solidarity of coffee farmers in Kayanza province. This article also highlights how mutualists behave with their social vulnerability.